Lagenorhynchus cruciger - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Lagenorhynchus cruciger (Quoy and Gaimard, 1824). Voy. autour du Monde.l'Uranie et la Physicienne, Zool., p. 87, pl. 2. TYPE LOCALITY: Pacific Ocean, "entre la Nouvelle-Hollande et le cap Horn [= between Australia and Cape Horn],.par 49° [S] de latitude". DISTRIBUTION: Southern Hemisphere: antarctic and cold-temperate waters. STATUS: CITES - Appendix II. SYNONYMS: albigena, bivattus, clanculus, wilsoni. COMMENTS: Formerly included australis and obscurus, see Hershkovitz (1966«) and comments under australis and obscurus. Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 353, DOI: 10.5281/zenodo.7352970